First trimester placental growth factor and uterine artery pulsatility index in the prediction of preeclampsia in high-risk pregnancy - Jasmin Hodžić; Bedrana Muračrvić; Ajna Gračić; Hana Štimjanin Hodžić; Ema Bajgorić Škrgo (Medicinski glasnik, 2025)
Aim: To identify the most effective screening method for preeclampsia by evaluating the predictive significance of measuring serum placental growth factor (PlGF) concentration and using Doppler ultrasound assessments of uterine artery blood flow during the first trimester in high-risk pregnancies as predictors of preeclampsia. Methods: A prospective screening study involving 173 high-risk pregnant women for preeclampsia, between 11 + 0 and 13 + 6 weeks of gestation was conducted. Women were divided into two groups based on pregnancy outcome: a control group of 158 pregnant women who remained normotensive, and a group of 15 high-risk pregnant women who developed symptoms of preeclampsia during pregnancy. Serum PlGF concentration using a quantitative enzyme-linked immunosorbent assay was determined. Results: PlGF level was significantly reduced in women who later developed preeclampsia (14.06 pg/mL) compared to controls (37.46 pg/mL). The uterine artery pulsatility index (UtA-PI) was significantly increased in the preeclamptic group (1.73) compared to the control group (1.44). For screening preeclampsia using the combination of PlGF and UtA-PI, the estimated detection rates were 66.67% at the fixed false-positive rate (FPR) of 5% and 73.33% at the FPR of 10%. The best screening results were obtained using regression models including maternal characteristics PlGF, and UtA-PI, yielding estimated detection rates of 73.33% at the FPR of 5% and 86.67% at the FPR of 10%, respectively. Conclusion: Placental growth factor level, in conjunction with uterine artery pulsatility index during the first trimester was a valuable and accurate biomarker for predicting preeclampsia in high-risk pregnancies. When integrated with comprehensive medical history, these markers enhance the assessment of preeclampsia risk.
Keywords: biomarkers; placenta growth factor; pre-eclampsia; uterine artery